أثر جدولة التمرين المكثف بأسلوب الراحة القليلة في تعلم مهارة التمريرة الصدرية بكرة السلة - النائب، رشا قيدار عبدالحميد; السويدي، أحمد حامد أحمد (جامعة الموصل - كلية التربية الرياضية, 2023)
هدف البحث إلى التعرف على ما يأتي: -الكشف عن أثر أسلوب جدولة التمرين المكثف بأسلوب الراحة القليلة في تعلم مهارة التمريرة الصدرية الهجومية بكرة السلة بين الاختبارين القبلي-البعدي. واستخدم الباحثان المنهج التجريبي لملاءمته لطبيعة ومشكلة البحث، وتكون مجتمع البحث من طلبة السنة الدراسية الأولى في قسم التربية البدنية وعلوم الرياضة/ كلية التربية الأساسية/ جامعة الموصل للعام الدراسي (۲۰۲۱-۲۰۲۲) والبالغ عددهم (٧٤) طالبا وطالبة، ويمثلون قاعة دراسية واحدة. أما عينة البحث فقد تم اختيارها بالطريقة العمدية بعد استبعاد الطالبات والبالغ عددهن (١٦) طالبة، لذا فقد بلغت عينة البحث (١٦) طالبا، واستخدم الباحثان الاختبارات المهارية لقياس أهداف البحث، وتم التحقق من صدق الاختبارات وثباتها بالطرائق الإحصائية المناسبة وأشارت نتائج الدراسة إلى الاستنتاج الآتي: -أثرت البرنامج التعليمي الخاصة بجدولة التمرين المكثف بفترات راحة قليلة إيجابية في تعلم مهارة التمريرة الصدرية بكرة السلة. ويوصي الباحثان بما يأتي: -استخدام المنهاج التعليمية الخاصة بجدولة التمرين المكثف بأسلوب الراحة القصيرة على عينة من الطالبات. The research aims to identify the following: -Detecting the effect of the method of scheduling the intensive exercise with the method of short rest on learning the skill of the offensive chest pass in basketball between the two pre-and post-tests. The researchers used the experimental approach due to its suitability to the nature and problem of the research, and the research community consisted of first-year students in the Department of Physical Education and Sports Sciences/ College of Basic Education/ University of Mosul for the academic year (2021-2022), whose number is (74) students, and they represent a classroom one. As for the research sample, it was chosen by the intentional method after excluding the female students, whose number is (16) female students, so the research sample reached (16) male students, and the researchers used skill tests to measure the objectives of the research, and the validity and reliability of the tests were verified by appropriate statistical methods. The study reached the following conclusion: -The educational program of intensive exercise scheduling with few rest periods had a positive impact on learning the skill of the basketball chest pass. The researcher recommended the following: The use of educational curricula for scheduling intensive exercise with a short rest method on a sample of female students
Keywords: البرامج التعليمية -- التدريبات المكثفة -- رياضة كرة السلة -- المهارات الهجومية -- التمريرة الصدرية